PENGEMBANGAN MATERI PAI MELALUI PENGAYAAN DENGAN BERBAGAI SUMBER BELAJAR - -, Siti Khoirun Nisak (Al Tadib : Jurnal Ilmu Pendidikan, 2021)
In Islamic Education learning, the demands of the curriculum require students not only to master theoretical information but how this information can be developed according to the needs of the area and environment in which students live. By paying attention to the principles of individual differences (initial abilities, intelligence, personality, talents, potential, interests, motivation to learn, learning styles), the enrichment program is carried out to fulfill children's needs. Educators to develop Islamic Education materials should use several kinds of learning resources in this enrichment according to the situation at hand, and be adjusted to the costs or economic conditions of the educators themselves and students so that they run continuously and not be burdensome in the future.